Precision therapy to target apoptosis in prostate cancer - Kulik, G. (Experimental Oncology, 2014)
Androgen-independent prostate cancer shows limited response to existing systemic therapies. Recent advances in prostate-selective targeting of small molecule inhibitors and bacterial toxins have created opportunities to design a new generation of therapies for advanced prostate cancer. Yet prioritizing targets for these therapies remain challenging, since multiple mechanisms contribute to the pathophysiology of androgen-independent prostate cancer. This review explores the possibility of targeting the apoptosis regulatory network as most direct approach to efficient treatment of advanced androgen-independent prostate cancer. Key Words: prostate cancer, apoptosis, prostate-selective therapies, PSA-activated pro-drugs, PSMA-targeting toxins.